2017
DOI: 10.1177/0022034517702094
|View full text |Cite
|
Sign up to set email alerts
|

Fissure Seal or Fluoride Varnish? A Randomized Trial of Relative Effectiveness

Abstract: Fissure sealant (FS) and fluoride varnish (FV) are effective in preventing dental caries when compared with a no-treatment control. However, the relative clinical effectiveness of these interventions is uncertain. The objective of the study was to compare the clinical effectiveness of FS and FV in preventing dental caries in first permanent molars (FPMs) in 6- to 7-y-olds. The study design was a randomized clinical trial, with 2 parallel arms. The setting was a targeted-population program that used mobile dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 22 publications
1
40
1
4
Order By: Relevance
“…In terms of the cost-effectiveness of fluoride varnish programmes, a recently published study of a community oral health programme compared fluoride varnish with fissure sealants in caries-free 6-to 7-year-olds in an area with a high caries risk in Wales. No differences in caries prevention effect were found, but fluoride varnish proved to be less expensive and probably more cost-effective in the longer perspective [Chestnutt et al, 2017].…”
Section: Discussionmentioning
confidence: 85%
“…In terms of the cost-effectiveness of fluoride varnish programmes, a recently published study of a community oral health programme compared fluoride varnish with fissure sealants in caries-free 6-to 7-year-olds in an area with a high caries risk in Wales. No differences in caries prevention effect were found, but fluoride varnish proved to be less expensive and probably more cost-effective in the longer perspective [Chestnutt et al, 2017].…”
Section: Discussionmentioning
confidence: 85%
“…Other longitudinal studies observed that partial or total loss of the material occurred, but retention did not influence treatment success [13,21,23], and although they are not noticed, sealant particles are retained and block the deeper parts of pits and fissures releasing fluorine [17,24].…”
Section: Discussionmentioning
confidence: 93%
“…Although studies have shown resinous materials as the material of choice, there are still gaps in showing the best evidence to put into clinical practice [16][17][18][19][20]. Previous studies have shown that transversal brushing and ionomeric sealing techniques may have similar efficacy [13,21]. After that, the important relevance of the theme by comparing techniques in social actions was verified and thus, to fill the gaps and make feasible the planning and execution of social programs aimed at the oral health of the population.…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that sealing S51 permanent molars in all patients further improves the outcome, adding only a small incremental cost relative to risk-based sealing [5]. Another study concluded that sealing primary molars reduces restorations and extractions and ensures an oral environment with less risk factors for recently erupted permanent teeth [6].…”
Section: Background and Aimsmentioning
confidence: 99%